2015
DOI: 10.1002/2015ja021517
|View full text |Cite
|
Sign up to set email alerts
|

Large‐amplitude GPS TEC variations associated with Pc5–6 magnetic field variations observed on the ground and at geosynchronous orbit

Abstract: Large‐amplitude variations in GPS total electron content (TEC) at Pc5–6 (<6.67 mHz) frequencies have been observed, using a high data rate Global Positioning System (GPS) receiver of the Canadian High Arctic Ionospheric Network. TEC variations with peak‐to‐peak amplitudes of 2–7 TEC units (1 TECU = 1016 el m−2) were observed over a 2.5 h period in the postnoon sector on 9 September 2011, during a period of high auroral activity within a moderate geomagnetic storm. TEC observations were from the Sanikiluaq, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 47 publications
0
41
1
Order By: Relevance
“…However, GPS observations have revealed that the depth of periodic TEC modulation is sometimes even somewhat larger (e.g., in the event of October 31, 2003, ΔN T /N T ~ 2.5 %) than the geomagnetic field modulation (ΔB/B 0 ~ 1 %). In principle, ULF modulation of energetic electron precipitation, inducing an additional periodic ionization of the lower ionosphere, can cause periodic TEC variations with much higher depth than geomagnetic field variations (Watson et al 2015). However, during the event under consideration no periodic electron precipitation occurred as evidenced by simultaneous riometer observations.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, GPS observations have revealed that the depth of periodic TEC modulation is sometimes even somewhat larger (e.g., in the event of October 31, 2003, ΔN T /N T ~ 2.5 %) than the geomagnetic field modulation (ΔB/B 0 ~ 1 %). In principle, ULF modulation of energetic electron precipitation, inducing an additional periodic ionization of the lower ionosphere, can cause periodic TEC variations with much higher depth than geomagnetic field variations (Watson et al 2015). However, during the event under consideration no periodic electron precipitation occurred as evidenced by simultaneous riometer observations.…”
Section: Discussionmentioning
confidence: 98%
“…The radar observations showed that Pc5 waves can noticeably modulate the ionospheric plasma: the electric field E, plasma convection velocity V, E-layer electron density N e and the ionosphere conductance Σ, and electron T e and ion T i temperatures in both F-and E-layers (see references in Pilipenko et al 2014b). Recent observations by Pilipenko et al (2014a) and Watson et al (2015) have demonstrated that Pc5 waves are capable to modulate TEC as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For an examination of the ionospheric response to solar wind pressure pulses, Jayachandran et al (2011) suggested using the GPS global navigation satellite system. This technique that provides information on total electron content (TEC) along a radio path satellite-ground receiver is sensitive enough to detect the ionospheric response to transient and periodic disturbances in the ULF band (Watson et al 2015;Belakhovsky et al 2016). The case study of a TEC response to an IP shock by Jin et al (2016) suggested that a shock-generated TEC variation is a "duplication" of the shock aurora observed by UV sensors onboard the Defense Meteorological Satellite Program (DMSP) satellites.…”
Section: Introductionmentioning
confidence: 99%